Disobedience : a novel - Hamilton, Jane (New York : Doubleday, 2000)
Henry Shaw, a high school senior from an average upper-middle-class Chicago family, discovers that his mother, a pianist, is having an affair when he accidentally reads her e-mail.
Keywords: Adultery -- Fiction; Domestic fiction